Suffering and prejudice: Do negative emotions predict immigration concerns? - Sumit S. Deole; Yue Huang (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2023)
This paper examines the role of individuals' emotions in determining their concerns about international migration. For the empirical analysis, we exploit the previously less explored information in the German Socio-Economic Panel (SOEP) data on individuals' negative emotions, e.g., anger, fear, and sadness. We find that the increased frequency of experiencing negative emotions is positively associated with immigration concerns. Moreover, we show that the relationship varies across employment status, birth cohort, and social media usage. Our analysis also underscores the real-life consequence of emotions by demonstrating their positive association with male support for far-right political parties but not among females. Finally, we exploit the exogenous variation in negative emotions induced by individuals' parent's death to infer causality. Fixed effects regressions with instrumental variables exhibit a positive impact of negative emotions on immigration concerns only among females, but no significant effects are found among males. We discuss the results for their robustness and limitations.
Keywords: D91; F22; P16; 330; Negative emotions; immigration concerns; bereavement